Dislocation Etching Morphology on the A Plane of Sapphire Crystal. Issue 9 (12th June 2021) - Cao, Fuyang; Li, Fei; Yuan, Zhiyong; Zhang, Lunyong; Jiang, Sida; Shen, Hongxian; Ning, Zhiliang; Huang, Yongjiang; Xing, Dawei; Zuo, Hongbo; Han, Jiecai; Sun, Jianfei
Abstract: In this work, the dislocation etching pit morphology and etching kinetics on the A ‐{11 2 ¯ 0} plane of sapphire crystal (α‐Al2 O3 ) are studied experimentally. The results show that the etch pit exhibits a subrhombic 3D morphology, which is consistent with the atom arrangement symmetry of the A plane. Further analysis shows that the two adjacent sides of the rhombic etch pits correspond to the directions [3 3 ¯ 0 1 ¯ ] and [3 3 ¯ 02], respectively; both of them are in the atomic close‐packing direction of A plane. The etch pits are controlled by a chemical reaction between Al2 O3 and potassium hydroxide (KOH) with the reaction activation energy of 51.7 kJ mol −1, which is developed in a manner of kinematic wave by the step moving with a constant speed. Abstract : The dislocation etching pits on the A ‐{11 2 ¯ 0} plane of sapphire are introduced by molten potassium hydroxide (KOH). The etching pits exhibit a subrhombic 3D morphology, which is determined by atomic arrangement symmetry of the A ‐{11 2 ¯ 0} plane. The etching kinetics is revealed to follow the Arrhenius' law, with an activation energy of about 51.7 kJ mol −1 .